A comparative study of physico-mechanical, bioactivity and hemolysis properties of pseudo-wollastonite and wollastonite glass-ceramic synthesized from solid wastes. Issue 1 (January 2020) - Hossain, SK S.; Yadav, Sushma; Majumdar, Shreyasi; Krishnamurthy, S.; Pyare, Ram; Roy, P.K.
Abstract: This study aims to synthesize pseudo-wollastonite and wollastonite base glass-ceramic from solid wastes, and a comparative study of their physico-mechanical, bioactivity, and hemolysis properties is conducted. The stoichiometric amount of chicken eggshells derived CaO (~99%), and rice husk ash (RHA) derived nano SiO2 (~99%) is used as ingredients for the formulation of wollastonite. The pseudo-wollastonite (α-W) is synthesized by sintering the ingredients at 1200 °C for 4 h, and wollastonite glass is made through the quenching method after melting of the ingredients at 1400 °C. The wollastonite glass-ceramic (GC) is prepared by control heat-treatment of wollastonite glass at 1200 °C for 1 h. Numerous characterizations like X-ray diffraction (XRD), scanning electron microscopy (SEM), apparent porosity and bending strength of α-W and GC are comparatively investigated. The GC is composed of the collaborative pseudo-wollastonite nucleation (~35%) and amorphous phases. α-W and GC show the apparent porosity about 4.23 % and 2.77 %, bending strength about 108 MPa and 139 MPa, and an average grain size about 2.30 μm and 0.60 μm, respectively. The obtained results exhibit that the waste-derived both α-W and GC have excellent bioactivity and good hemolysis index (<2%). Moreover, GC shows slightly more hydroxyapatite (HA) layer formation ability than α-W in the simulated body fluid (SBF) solution. This comparative study of α-W and GC is recommended that the GC is offering more promising characteristics for biomedical applications. Highlights: Waste rice husk ash and eggshells are used as starting ingredients. Pseudo-wollastonite (α-W) and wollastonite glass-ceramic (GC) are synthesized. The α-W and GC both have exhibited excellent bioactivity and hemolysis index (<2%). GC shows more favorable characteristics for biomedical applications than α-W.